Chronic kidney disease as a potential risk factor for retinal vascular disease: A 13-year nationwide population-based cohort study in Taiwan. Issue 15 (16th April 2021) - Lin, Chun-Ju; Tien, Peng-Tai; Lai, Chun-Ting; Hsia, Ning-Yi; Chang, Cheng-Hsien; Yang, Yu-Cih; Bair, Henry; Chen, Huan-Sheng; Wu, Wen-Chuan; Tsai, Yi-Yu
Abstract : Abstract: We investigate whether patients with chronic kidney disease (CKD) are at increased risk of retinal vascular disease (RVD). Data was collected from the Taiwan National Health Insurance system and included patients newly diagnosed with CKD between 2000 and 2012. The endpoint of interest was a diagnosis of RVD. Follow-up data of 85, 596 patients with CKD and 85, 596 matched comparisons (non-CKD) from 2000 to 2012 were analyzed. Patients with CKD were found to have a significantly higher cumulative incidence of RVD (Kaplan–Meier analysis, log-rank test P  < .0001). Through multivariate Cox regression analysis, the CKD group was found to have higher risk of developing RVD (adjusted hazard ratio (HR) [95% confidence interval (CI)]: 2.30 [2.16–2.44]) when compared to the control cohort. When comparison of CKD group and non-CKD group was stratified by gender, age and comorbidities (hypertension, diabetes, and hyperlipidemia), the higher risk of RVD in patients with CKD remained significant in all subgroups. Patients with CKD were found to have higher risk of developing RVD in this cohort study. In addition, CKD imposed the same risk for RVD development in all age groups and in patients with or without hypertension or diabetes. Thus, patients with CKD should be vigilant for symptoms of RVD. Understanding the link between CKD and RVD could lead to the development of new treatment and screening strategies for both diseases. Abstract : Supplemental Digital Content is available in the text